COMPARATIVE STUDY ON THE MEASUREMENT OF LIVER T2* VALUES OF THALASSEMIA PATIENTS AND THE CLINICAL GRADING OF LIVER IRON CONCENTRATION BY DIFFERENT POST-PROCESSING SOFTWARE - Peng Peng; Fengming XU; Jixing YI; Bumin LIANG; Cheng TANG; Qing FENG (Mediterranean Journal of Hematology and Infectious Diseases, 2022)
Objective: To explore the relationship between the liver T2* values of thalassemia patients measured by Circle Cardiovascular Imaging CVI42 (CVI42), CMRtools / Thalassemia Tools (CMRtools) and Excel spreadsheet (Excel), and the three software's accuracy in clinical grading of liver iron concentration (LIC). Methods: The liver T2* images thalassemia patients were imported into CVI42 and CMRtools to measure the T2* value. And the signal intensity (SI) of the T2* image, measured in the MR scanning equipment, was input into Excel to calculate T2* value. The relationship of the T2* values measured by the above three software were compared. And LIC clinical grading was performed on the three measured T2* value results, and the LIC (LICF) provided by FerriScan was used as the reference standard to compare the accuracy of the three grading results. Results: There was no statistical difference between the T2* values measured by CVI42, CMRtools and Excel (P>0.05), but there was a high degree of consistency between them (P<0.05), and there was a high linear positive correlation between the them (P<0.05). There was no statistical difference between the LIC grading results of CVI42 and CMRtools and the LICF grading results (P>0.05). There is a significant difference between the LIC grading results of Excel and the LICF grading results (P<0.05). Conclusion: The liver T2* values measured by CVI42, CMRtools and Excel are equivalent. However, CVI42 and CMRtools have better diagnostic accuracy for LIC clinical grade, while Excel has worse diagnostic accuracy.